Enhanced chromium tolerance of La0.6Sr0.4Co0.2Fe0.8O3 − δ electrode of solid oxide fuel cells by Gd0.1Ce0.9O1.95 impregnation - Zhao, L.; Amarasinghe, S.; Jiang, San Ping (2013)
The electrochemical activities and chromium tolerances are studied on single phase La0.6Sr0.4Co0.2Fe0.8O3 − δ (LSCF) and Gd0.1Ce0.9O1.95 (GDC) impregnated LSCF (GDC-LSCF) cathodes of solid oxide fuel cells (SOFCs). GDC-LSCF electrode shows a significantly reduced electrode polarization resistance and more stable performance for the O2 reduction reaction in the presence of chromia-forming metallic interconnect as compared to that on LSCF. The results indicate that the impregnated GDC nanoparticles serve as a barrier layer to enhance the resistance and tolerance of LSCF towards chromium deposition and poisoning.